2019
DOI: 10.3390/su11154198
|View full text |Cite
|
Sign up to set email alerts
|

Communication Factors Affecting Tourist Adoption of Social Network Sites

Abstract: Smart tourism technologies (STTs) are technological media that tourists apply in various stages of the tourism decision-making process. The purpose of this study was to explore how the communication elements of social network sites (SNSs), as a part of STTs, enhance tourists' motivation and usage intention. A structural framework based on communication elements and the uses and gratification theory with regard to SNSs usage was developed and investigated. An online survey was employed for the data collection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 66 publications
(89 reference statements)
2
8
0
1
Order By: Relevance
“…In addition, explorative use has a strong influence on overall tourism experience satisfaction, and exploitative use mainly enhances the transaction satisfaction. A study by Ho and Gebsombut [62] aimed to explore how the communication elements of SNSs, as a part of ST technologies, enhance tourists' motivation and usage intentions. The findings indicate that the information-seeking motive, entertainment motive, relationship maintenance motive and Internet self-efficacy positively influence the intention to use SNSs for trips.…”
Section: The Impact Of Sm/snss On Tourist Behaviormentioning
confidence: 99%
“…In addition, explorative use has a strong influence on overall tourism experience satisfaction, and exploitative use mainly enhances the transaction satisfaction. A study by Ho and Gebsombut [62] aimed to explore how the communication elements of SNSs, as a part of ST technologies, enhance tourists' motivation and usage intentions. The findings indicate that the information-seeking motive, entertainment motive, relationship maintenance motive and Internet self-efficacy positively influence the intention to use SNSs for trips.…”
Section: The Impact Of Sm/snss On Tourist Behaviormentioning
confidence: 99%
“…Media stickiness increases in line with the individual's perceived value of social media content [44]. Recent research has highlighted that gratifications are key drivers of social media use [33,35,37]. Reference [45] found that entertainment, expressive information sharing, and social interaction gratifications predict online travel communities' ability to retain users.…”
Section: Effects Of the Gratifications Provided By Social Media Use On Consumer Interactive Behaviourmentioning
confidence: 99%
“…La teoría de UyG explica por qué la audiencia utiliza un determinado medio de comunicación y qué gratificaciones reciben de este uso (McQuail, 1994;Dhir et al 2017;Parmelee y Roman, 2019). Asimismo, es una herramienta que sirve para explicar las motivaciones de consumo de medios tradicionales, pero también ha sido considerada muy adecuada en la investigación de las motivaciones para usar las redes sociales, y en concreto, Facebook (Choi et al, 2016;Hur et al 2017;Plume y Slade, 2018;Ho y Gebsombut, 2019).…”
Section: Usos Y Gratificacionesunclassified